ANALISIS PENINGKATAN KUALITAS MANUFACTURE SWITCHGEAR SM6 DENGAN METODE DMAIC UNTUK MENGURANGI TINGKAT MANUFACTURE DEFECT RATE (MDR) DI PT. SCHNEIDER ELECTRIC INDONESIA CIKARANG PLANT - Benny Ferdyan (Operations Excellence: Journal of Applied Industrial Engineering, 2015)
Abstract. The aim of this study is to determine the Sigma Level of SM6switchgear production at PT. SCP, knowing the cause of Manufacture Defect Rate(MDR) high and propose improvements in the quality of production through theanalysis of Six Sigma DMAIC method. The result showed the level of Sigma hasachieved of company target but only six month. The root cause of the problem ofhigh MDR is caused by three factors: Material, Man, and Method. Proposedimprovements is hiring quality assurance design to solve drawing error,engineering design must informed to the related team when there are changes ondrawing, standardize the material to reduce variations in type of component, add3M double-tape adhesive or replace material with traffolyte label for problemlabel component are easily separated. Proposed improvements to the problems onman factors with training scheduled on an ongoing basis about wiring skills,knowledge of type of component in the panel as well as the importance ofmaintaining quality management in the production process. Proposedimprovements to the problems on Method factors is socialization and supervisionof the implementation of the working procedures.Keywords: Quality improvement, Six Sigma, Defect rate, DMAIC